PERANAN ORGANISASI UNI EROPA DALAM MENGATASI KRISIS KEUANGAN NEGARA YUNANI - Pahlevi, Pahlevi; Riezky, Raden Mohammad (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The role of the European Union Organization in overcoming the Greek State financial crisis by running the Economic Adjustment Program(Economic savings Program) implemented by the Greek Government. The data used are secondary data because the scientific research of International Relations uses qualitative data. The data collection method used in this study is the literature of books, websites. Techniques of data analysis using qualitative analysis. The results of the study indicate that the European Union Organization succeeded in getting the Greek State out of its financial crisis.